Casangrá: casas que sangram - FRANÇA, Tarsila Maquiavel Rosa de (2023)
This scientific article has a reflexive approach on the artistic creative process of the show Casangrá presented at Teatro Universitário Cláudio Barradas in November 2022. Casangrá debates about domestic services which still exist in our daily lives. It has precisely focused on domestic worker(maid) and child maid called as cria de família. Oral memory and write-living were used as a methodology to construct this project. The resulting dramaturgy flirts with comedy and hybrid staging that through scenic elements speak of the Amazonian reality. It is through this creative process we will discuss the condition of peripheral women in current society related them to historical capitalism processes and their impacts on race and gender. Finally, the article Casangrá is a feminist manifesto that deals with the creation process of Tarsila Rosa's first show focused on staging and dramaturgy.